Disappearing signs. Can the changes in The Polish chivalric coats-of-arm s be traced in medieval sources? - GIGOŃ, MATEUSZ (Journal of Education Culture and Society, 2020)
The paper presents an overview of current papers(but it reminds us also of fi ndings of prewar researchers) about coats-of-arms of small chivalric clans, rarely present in sources. It also contains some fi ndings made by the author himself, mainly about Prus, Chmara and Zgraja coats-of-arms. The intent of the author was also a limited sources study refl ec-tion on the coats-of-arms, about which there is lack of information concerning their shape and probable genetical relationship with other coats-of-arms. The following coats-of-arms or their callings were mentioned: Kliza, Wiza, Moszczenica, Calina, Wazanki, Piękostki, Ulina, Owada, Czawuja, Kołmasz, Prus I (Turzyna), Prus II (Wilczekosy), Glezyna, Lary-sza, Ogniwo, Zarosie, Chmara, Zgraja, Goljan. Most of them turned out to equate with other, better known coats-of-arms, or strove for that kind of equation. All this makes the structure of polish medieval society and the rules of that society more clear